THE EFFORTS TO IMPROVE SCHOOL QUALITY REPORT CARD WITH A COLLABORATIVE MANAGEMENT SYSTEM AT TEGALWARU STATE VOCATIONAL SCHOOL - Riyadi, Jaka Slamet (Pergunu Jawa Barat, 2025)
This study aims to analyze efforts to improve school quality reports through a collaborative management system at Tegalwaru State Vocational High School. The background of this research is based on the importance of synergy among school stakeholders, including the principal, teachers, education staff, and external parties, in improving the quality of education in accordance with the National Education Standards (SNP). The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that implementing a collaborative management system involving all school components can improve the achievement of quality indicators, such as graduate competencies, learning processes, and school management. Supporting factors for success include participatory leadership, effective communication, and the use of information technology. Barriers encountered include limited resources and a lack of awareness of the importance of collaboration on the part of some parties. In conclusion, the collaborative management system is an effective strategy for improving school quality reports and can therefore be recommended for sustainable implementation.